THE EFFECT OF IMPLEMENTATION OF PERFORMANCE BUDGET AND INTERNAL CONTROL ON PERFORMANCE ACCOUNTABILITY WITH INFORMATION SYSTEM AS A MODERATING VARIABLE IN VERTICAL HOSPITAL - Brahmana, Herika Debora (Asosiasi Dosen Akuntansi Indonesia, 2018)
The purpose of this study was to analyze the effect of performance budget implementation, internal control on the performance accountability of government agencies and information systems as moderating variables in the Vertical Hospital of the Directorate General of Health Services. The type of research used is causal research with a quantitative approach. The population in this study were all Vertical Hospitals of the Ministry of Health of Indonesia as many as 33 hospitals and Inspectorate General of the Ministry of Health. The research method uses census method, that is, all populations in this study are used as research samples. Data analysis method uses multiple linear regression l mode and interaction test for moderating variables. The results of this study indicate that simultaneously performance budget implementation and internal control have a significant effect on the performance accountability of agencies of the Vertical Hospital of the Directorate General of Health Services. Partially only performance budget implementation has a significant positive effect on the performance accountability of government agencies, while internal control variables do not affect the performance accountability of government agencies. Information systems as moderating variables cannot strengthen the relationship between performance budget implementation and internal control with the performance accountability of government agencies Vertical Hospital Directorate General of Health Services.